Herbivore exclusion stabilizes alpine grassland biomass production across spatial scales - Juntao Zhu; Yangjian Zhang; Jianshuang Wu; Xianzhou Zhang; Guirui Yu; Zhenxi Shen; Xian Yang; Yunlong He; Lin Jiang; Yann Hautier (Global Change Biology, 2024)
There is growing evidence that land‐use management practices such as livestock grazing can strongly impact the local diversity, functioning, and stability of grassland communities. However, whether these impacts depend on environmental condition and propagate to larger spatial scales remains unclear. Using an 8‐year grassland exclosure experiment conducted at nine sites in the Tibetan Plateau covering a large precipitation gradient, we found that herbivore exclusion increased the temporal stability of alpine grassland biomass production at both the local and larger (site) spatial scales. Higher local community stability was attributed to greater stability of dominant species, whereas higher stability at the larger scale was linked to higher spatial asynchrony of productivity among local communities. Additionally, sites with higher mean annual precipitation had lower dominant species stability and lower grassland stability at both the spatial scales considered. Our study provides novel evidence that livestock grazing can impair grassland stability across spatial scales and climatic gradients.